Van Wyk Louw in ligter luim - van Rensburg, F.I.J. (Tydskrif vir Letterkunde, 2006)
Throughout the years students of the work of N.P. van Wyk Louw tended to focus on its preoccupation with the “deeper” aspects of life, thereby losing sight of the wide spectrum of “surface” or lighter aspects contained in it, not only of a thematic, but also of a structural nature. Concentrating on the linguistic structure of a number of texts, a wide range of creative strategies based on playfulness was identified. The article explores this aspect of his work, particularly in his poetry, his theatrical work, and his reflective prose.